2020
DOI: 10.5194/acp-20-11287-2020
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Leaf-scale gas exchange of atmospheric reactive trace species (NO<sub>2</sub>, NO, O<sub>3</sub>) at a northern hardwood forest in Michigan

Abstract: Abstract. During the Program for Research on Oxidants: PHotochemistry, Emissions, and Transport (PROPHET) campaign from 21 July to 3 August 2016, field experiments on leaf-level trace gas exchange of nitric oxide (NO), nitrogen dioxide (NO2), and ozone (O3) were conducted for the first time on the native American tree species Pinus strobus (eastern white pine), Acer rubrum (red maple), Populus grandidentata (bigtooth aspen), and Quercus rubra (red oak) in a temperate hardwood forest in Michigan, USA. We measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 62 publications
0
15
0
1
Order By: Relevance
“…For example, emissions of biogenic volatile organic compounds (BVOCs) from vegetation contribute to the formation of tropospheric ozone and secondary organic aerosol, both air pollutants and short‐lived climate forcers (Fehsenfeld et al., 1992; Fiore et al., 2012; Hallquist et al., 2009; Henze & Seinfeld, 2006; Trainer et al., 1987). Air pollution and the atmospheric oxidizing capacity also depend on NO x (=NO + NO 2 ) (Crutzen, 1974, 1979; Levy, 1971), which has a soil source and a vegetation sink (Delaria et al., 2018; Jacob & Bakwin, 1991; Wang et al., 2020; Yienger & Levy, 1995). A key but overlooked component of forest‐atmosphere chemical exchanges is turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…For example, emissions of biogenic volatile organic compounds (BVOCs) from vegetation contribute to the formation of tropospheric ozone and secondary organic aerosol, both air pollutants and short‐lived climate forcers (Fehsenfeld et al., 1992; Fiore et al., 2012; Hallquist et al., 2009; Henze & Seinfeld, 2006; Trainer et al., 1987). Air pollution and the atmospheric oxidizing capacity also depend on NO x (=NO + NO 2 ) (Crutzen, 1974, 1979; Levy, 1971), which has a soil source and a vegetation sink (Delaria et al., 2018; Jacob & Bakwin, 1991; Wang et al., 2020; Yienger & Levy, 1995). A key but overlooked component of forest‐atmosphere chemical exchanges is turbulence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated a maximum leaf-level NO 2 compensation point of 1-3 ppb (Raivonen et al, 2009;Teklemariam & Sparks, 2006, and references therein), while the minimum observed ambient NO 2 levels at Bosco Fontana are ±3 ppb. Additionally, recent observational evidence suggests that this value does not differ significantly from zero (Delaria et al, 2018;Wang et al, 2020).…”
Section: Soil No X Exchangementioning
confidence: 76%
“…Previous studies have indicated a maximum leaf‐level NO 2 compensation point of 1–3 ppb (Raivonen et al., 2009; Teklemariam & Sparks, 2006, and references therein), while the minimum observed ambient NO 2 levels at Bosco Fontana are ±3 ppb. Additionally, recent observational evidence suggests that this value does not differ significantly from zero (Delaria et al., 2018; Wang et al., 2020).…”
Section: Methodsmentioning
confidence: 88%